1996
DOI: 10.1111/j.1476-5381.1996.tb15237.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of nicorandil, pinacidil and nitroglycerin on hypoxic and hypercapnic pulmonary vasoconstriction in the isolated perfused lung of rat

Abstract: 1 The aims of this study were to compare in the rat isolated perfused lung preparation, the dilator actions of nicorandil, pinacidil and nitroglycerin on the hypoxic pulmonary pressure response with or without hypercapnic acidosis and to investigate the possible involvement of K channels and EDRF in these effects. 2 Isolated lungs from male Wistar rats (260-320 g) were ventilated with 21%02 + 5%CO2 + 74%N2 (normoxia) or 5%CO2+95%N2 (hypoxia) and perfused with a salt solution supplemented with ficoll and gassed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…The same group also showed that in the isolated cat lung, acidosis caused vasoconstriction at low and at high vascular tone. In contrast, Dumas et al showed that HPV was enhanced by acidosis and suggested that K π channels may be involved, and that the effects of acidosis are independent of NO pathway (7). Our results support the notion that nitric oxide does not play a major role in changes in vascular tone during acidosis and alkalosis in rat lungs (5,7).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The same group also showed that in the isolated cat lung, acidosis caused vasoconstriction at low and at high vascular tone. In contrast, Dumas et al showed that HPV was enhanced by acidosis and suggested that K π channels may be involved, and that the effects of acidosis are independent of NO pathway (7). Our results support the notion that nitric oxide does not play a major role in changes in vascular tone during acidosis and alkalosis in rat lungs (5,7).…”
Section: Discussionsupporting
confidence: 85%
“…These two agents cause contraction via mechanisms which activate receptor or voltage operated Ca 2π channels, respectively. Based on previous reports, we expected that during basal tone conditions alkalosis would cause vasodilation, and acidosis would cause vasoconstriction (4,5,7). We also expected that during elevated tone, acidosis may cause vasodilation (4)(5)(6).…”
Section: Discussionmentioning
confidence: 88%
“…Convincing evidence of the important role of vasoactive PGs in hypercapnic vasodilation was also demonstrated in a study involving the newborn pig brain. 32 Our experimental results showing hypercapnia-induced Ppa changes, which were not altered by NOS inhibition (Table 2), are qualitatively consistent with the findings of Dumas et al, 33 who demonstrated that inhibition of NO production did not potentiate the overall HPV under hypercapnic acidosis in the perfused rat lung. In a recent study involving mice in which the neuronal NOS was knocked out, Irikura et al 34 found that cerebrovascular dilatation by hypercapnia was reliably preserved, indicating that the NO-independent pathway plays a role in the response to hypercapnia in the brain as well.…”
Section: Intra-acinar Microvessel Vasodilatation Induced By Co 2 Molesupporting
confidence: 90%
“…54,57 This diversity in mechanisms of action of NO may be due to tissue as well as regional specificity in the expression of ion channels in vascular smooth muscles. 29 Along the same lines, although in heart and lung a significant role for K ATP channels has been reported in vasodilatation to PGI 2 , 10,11,59 our data with glibenclamide in ocular vasculature do not support an important role for K ATP ( Figure 5A and 5B).…”
Section: Discussionsupporting
confidence: 77%